Resin composition and semiconductor device

JP7641568B2Active Publication Date: 2025-03-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021090554
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-28
Publication Date
2025-03-07
Estimated Expiration
2041-05-28

AI Technical Summary

Benefits of technology

【0008】 本発明の一態様によると、成形して硬化させることで硬化物を作製した場合、硬化物の熱伝導性を高めやすく、かつ硬化物の弾性率を低減させやすく、さらに成形時の流動性が損なわれにくい樹脂組成物、及びこの樹脂組成物から作製された封止部を備える半導体装置を、提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641568000002
    Figure 0007641568000002
  • Figure 0007641568000001
    Figure 0007641568000001
Patent Text Reader

Abstract

To provide a resin composition which easily enhances the thermal conductivity of a cured product, easily reduces an elastic modulus of the cured product, and hardly impairs flowability during molding, when the cured product is manufactured by molding and curing.SOLUTION: A resin composition contains an epoxy resin (A), a curing agent (B), and an inorganic filler (C). The viscosity at 25°C of the epoxy resin (A) is 1500 mPa s or less. The inorganic filler (C) contains boron nitride (C1) having a median size of 0.1 μm or more and 2 μm or less and an average circularity of 0.80 or more. The percentage ratio of the boron nitride (C1) to the resin composition is 10 mass% or more and 30 mass% or less. The cured product of the resin composition has a bending elastic modulus at 25°C of 10 GPa or less, and a thermal conductivity of 1 W / m K or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a semiconductor device, and more particularly to a resin composition containing an epoxy resin and a semiconductor device having an encapsulating part which is a cured product of this resin composition. [Background technology]

[0002] Patent Document 1 discloses an underfill material applied to a semiconductor device. This underfill material contains an epoxy resin, a hardener, and a filler. The filler contains alumina. The alumina is surface-treated with aminosilane. Furthermore, the average particle size of the alumina is 2 μm to 10 μm. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-077771 A Summary of the Invention [Problem to be solved by the invention]

[0004] According to the inventor's research, when alumina is highly filled as an inorganic filler in a liquid underfill material for the purpose of increasing the thermal conductivity of the cured product, the elastic modulus of the cured product becomes too high, which makes it easy for internal stress to occur in the cured product, and therefore the reliability of the semiconductor device equipped with the underfill is likely to deteriorate. In addition, even if fused silica is highly filled as an inorganic filler, it is difficult to sufficiently increase the thermal conductivity of the cured product. In addition, the inventor has considered reducing the elastic modulus of the cured product by adding boron nitride to the inorganic filler, but boron nitride tends to increase the viscosity and thixotropy of the underfill material, which deteriorates the flowability of the underfill material during molding.

[0005] The object of the present invention is to provide a resin composition which, when molded and cured to produce a cured product, easily increases the thermal conductivity of the cured product, easily reduces the elastic modulus of the cured product, and is less likely to lose fluidity during molding; and to provide a semiconductor device having a sealing part made from this resin composition. [Means for solving the problem]

[0006] A resin composition according to an embodiment of the present disclosure contains an epoxy resin (A), a curing agent (B), and an inorganic filler (C). The epoxy resin (A) has a viscosity of 1500 mPa·s or less at 25°C. The inorganic filler (C) contains boron nitride (C1) having a median diameter of 0.1 μm or more and 2 μm or less and an average circularity of 0.80 or more. The percentage of the boron nitride (C1) relative to the resin composition is 10 mass% or more and 30 mass% or less. A cured product of the resin composition has a flexural modulus of 10 GPa or less and a thermal conductivity of 1 W / m·K or more at 25°C.

[0007] A semiconductor device according to an embodiment of the present disclosure includes a substrate, an electronic component mounted on the substrate, and a sealing portion that seals the electronic component. At least a portion of the sealing portion fills a gap between the substrate and the electronic component. The sealing portion is a cured product of the resin composition. Effect of the Invention

[0008] According to one aspect of the present invention, it is possible to provide a resin composition which, when molded and cured to produce a cured product, tends to increase the thermal conductivity of the cured product, tends to reduce the elastic modulus of the cured product, and is less likely to lose fluidity during molding; and a semiconductor device including a sealing part made from this resin composition. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a semiconductor device according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An embodiment of the present invention will be described below. Note that the present invention is not limited to the following embodiment. The following embodiment is merely a part of various embodiments of the present invention, and various modifications are possible depending on the design as long as the object of the present invention can be achieved.

[0011] The resin composition according to this embodiment (hereinafter also referred to as composition (X)) contains an epoxy resin (A), a curing agent (B), and an inorganic filler (C). The epoxy resin (A) has a viscosity of 1500 mPa·s or less at 25°C. The inorganic filler (C) contains boron nitride (C1) having a median diameter of 0.1 μm or more and 2 μm or less and an average circularity of 0.80 or more. The percentage of boron nitride (C1) relative to composition (X) is 10 mass % or more and 30 mass % or less. The cured product of the resin composition has a flexural modulus of 10 GPa or less and a thermal conductivity of 1 W / m·K or more at 25°C.

[0012] According to this embodiment, when a cured product is produced by molding and curing composition (X), the thermal conductivity of the cured product is easily increased, the elastic modulus of the cured product is easily reduced, and the fluidity of composition (X) during molding is less likely to be impaired.

[0013] This composition (X) can be used to produce a sealing portion 1 in a semiconductor device 10. As shown in Fig. 1, for example, a semiconductor device 10 including a sealing portion 1 produced from the composition (X) includes a substrate 3, an electronic component 2 mounted on the substrate 3, and a sealing portion 1 that seals the electronic component 2. At least a portion of the sealing portion 1 fills the gap between the substrate 3 and the electronic component 2. This sealing portion 1 is, for example, an underfill.

[0014] In this embodiment, it is easy to increase the thermal conductivity of the sealing portion 1 of the semiconductor device 10, and also easy to reduce the elastic modulus of the sealing portion 1. Therefore, even if the electronic component 2 generates heat, this heat is easily released from the electronic component 2 through the sealing portion 1. Furthermore, internal stress is unlikely to occur in the sealing portion 1, and therefore the reliability of the semiconductor device 10 is unlikely to be impaired. Furthermore, when the sealing portion 1 is produced from the composition (X), the flowability of the composition (X) is unlikely to be impaired, and therefore the composition (X) is easily caused to flow in the gap between the substrate 3 and the electronic component 2 and molded. Therefore, the moldability of the composition (X) is good.

[0015] This embodiment will be described in further detail below.

[0016] As described above, the composition (X) contains the epoxy resin (A), the curing agent (B) and the inorganic filler (C).

[0017] The epoxy resin (A) has a viscosity of 1500 mPa s or less at 25°C. This allows the composition (X) to flow easily. Therefore, when a sealing portion is made from the composition (X), the composition (X) can easily penetrate into the gap between the electronic component 2 and the substrate 3.

[0018] In the present embodiment, the resin may contain any one of a monomer, an oligomer, and a prepolymer. That is, the epoxy resin (A) may contain at least one selected from the group consisting of a monomer having an epoxy group, an oligomer having an epoxy group, and a prepolymer having an epoxy group.

[0019] The epoxy resin (A) contains, for example, at least one of an aromatic ring-containing epoxy resin and an alicyclic epoxy resin.

[0020] The aromatic ring-containing epoxy resin contains at least one selected from the group consisting of, for example, bisphenol F type epoxy resin, glycidylamine type epoxy resin, bisphenol A type epoxy resin, and naphthalene type epoxy resin.

[0021] The epoxy resin (A) preferably contains at least one selected from the group consisting of bisphenol F type epoxy resins, glycidylamine type epoxy resins, and alicyclic epoxy resins.

[0022] Bisphenol F epoxy resins have a lower viscosity than bisphenol A epoxy resins and naphthalene epoxy resins, and therefore tend to increase the fluidity of the composition (X).

[0023] Glycidylamine type epoxy resins are preferred because they have a lower viscosity than bisphenol F type epoxy resins. Furthermore, glycidylamine type epoxy resins tend to increase the glass transition temperature (Tg) of the cured product of the composition (X). When the epoxy resin (A) contains a glycidylamine type epoxy resin, the epoxy resin (A) preferably further contains a bisphenol F type epoxy resin. In this case, the glycidylamine type epoxy resin has high reactivity, but the reactivity of the entire epoxy resin (A) is moderately suppressed by the bisphenol F type epoxy resin. This makes it difficult for the fluidity of the composition (X) to be impaired when it is heated, and the storage stability of the composition (X) is easily maintained. The glycidylamine type epoxy resin preferably contains a glycidylamine type epoxy resin having three or more epoxy groups in one molecule (i.e., trifunctional or higher). In this case, the glass transition temperature of the cured product of the composition (X) tends to increase. Therefore, the heat resistance of the semiconductor device 10 having the sealing part 1 tends to increase.

[0024] The cycloaliphatic epoxy resin can include, for example, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and the like.

[0025] The epoxy equivalent of the epoxy resin (A) is preferably 90 g / eq or more and 170 g / eq or less. In particular, the epoxy equivalent of the bisphenol F type epoxy resin is preferably 150 g / eq or more and 170 g / eq or less. The epoxy equivalent of the glycidylamine type epoxy resin is preferably 90 g / eq or more and 100 g / eq or less. The epoxy equivalent of the alicyclic epoxy resin is preferably 120 g / eq or more and 140 g / eq or less.

[0026] When the epoxy resin (A) contains a bisphenol F type epoxy resin, the amount of the bisphenol F type epoxy resin is preferably 40 parts by mass or more and 80 parts by mass or less per 100 parts by mass of the total epoxy resin (A).

[0027] When the epoxy resin (A) contains a glycidylamine type epoxy resin, the content of the glycidylamine type epoxy resin is preferably 40 parts by mass or more and 60 parts by mass or less per 100 parts by mass of the total epoxy resin (A).

[0028] When the epoxy resin (A) contains an alicyclic epoxy resin, the content of the alicyclic epoxy resin is preferably 10 parts by mass or more and 30 parts by mass or less per 100 parts by mass of the epoxy resin (A). This can reduce the viscosity of the composition (X) before curing. In addition, it can suppress the decrease in the glass transition temperature (Tg) of the cured product of the composition (X).

[0029] The curing agent (B) is a compound that reacts with the epoxy resin (A) to cure the composition (X). The curing agent (B) contains at least one selected from the group consisting of amines such as aromatic amines, acid anhydrides, and phenol novolac resins.

[0030] The curing agent (B) preferably contains at least one of an aromatic amine and an acid anhydride. In this case, the adhesion between the cured product and the electronic component 2 and the substrate 3 is easily improved, and the cured product is less likely to absorb moisture. This improves the reliability of the semiconductor device 10 having the sealing portion 1.

[0031] The inorganic filler (C) can increase the thermal conductivity of the cured product, thereby improving the heat dissipation performance of, for example, the semiconductor device 10 including the sealing portion 1. Furthermore, the inorganic filler (C) can increase the strength of the cured product and reduce the linear expansion coefficient, thereby improving the reliability of, for example, the semiconductor device 10 including the sealing portion 1.

[0032] The percentage of the inorganic filler (C) in the composition (X) is preferably 70% by mass or more and 85% by mass or less. When this percentage is 70% by mass or more, the thermal expansion coefficient of the cured product is particularly easily reduced, the thermal conductivity of the cured product is particularly easily increased, and the elastic modulus of the cured product is also likely to be an appropriate value. When this percentage is 85% by mass or less, the fluidity of the composition (X) is particularly unlikely to be hindered, and the elastic modulus of the cured product is particularly unlikely to become excessively large. It is more preferable that this percentage is less than 78% by mass.

[0033] As described above, the inorganic filler (C) contains boron nitride (C1) having a median diameter of 0.1 μm or more and 2 μm or less and an average circularity of 0.80 or more. Boron nitride (C1) easily reduces the elastic modulus of the cured product, and therefore it is easy to realize that the bending elastic modulus of the cured product at 25° C. is 10 GPa or less. In addition, boron nitride (C1) is unlikely to impair the thermal conductivity of the cured product, and therefore it is easy to realize that the thermal conductivity of the cured product is 1 W / m·K or more. In addition, boron nitride (C1) is unlikely to inhibit the curing reaction of the epoxy resin (A) and is unlikely to reduce the glass transition temperature of the cured product. Therefore, boron nitride (C1) is unlikely to impair the heat resistance of the semiconductor device 10 having the sealing portion 1.

[0034] In addition, when the median diameter of boron nitride (C1) is 2 μm or less and the average circularity is 0.80 or more, boron nitride (C1) does not easily increase the viscosity of composition (X). Furthermore, when the average circularity of boron nitride (C1) is 0.80 or more, anisotropy is not easily generated in composition (X), and therefore the thixotropy of composition (X) is not easily increased excessively. Therefore, the fluidity of composition (X) is not easily impaired. In addition, when the median diameter of boron nitride (C1) is 0.1 μm or more, boron nitride (C1) is not easily aggregated in composition (X) and the cured product, and therefore the above-mentioned properties of composition (X) and the cured product are not easily impaired. The median diameter of boron nitride (C1) is more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. In addition, the median diameter of boron nitride (C1) is more preferably 1 μm or less.

[0035] The median diameter is calculated from the particle size distribution on a volume basis measured by a laser diffraction / scattering method. The same applies to the median diameters of materials other than boron nitride (C1) in this embodiment.

[0036] The circularity can be calculated by the following method. The circularity of materials other than boron nitride (C1) in this embodiment is similar. The area (number of pixels contained in the particle) and perimeter of the particle are obtained by observing the target particle using a microscope. For example, a VHX-6000 model manufactured by Keyence Corporation can be used as the microscope. From the measurement results, the circularity can be calculated by the following formula (1). In addition, appropriate image analysis software may be used to calculate the circularity. The average circularity is the average value of the circularity. That is, the circularity of each of a predetermined number of particles is measured, and the average value of these measured values ​​of circularity is the average circularity. The number of measurements of the circularity (the number of particles whose circularity is measured) is preferably as large as possible, for example, 30 or more.

[0037] Formula (1): Circularity = 4π × area / (perimeter) 2 (However, 0<circularity≦1) When the area of ​​a particle is less than 30 pixels, the "area" in formula (1) is the total number of pixels of the particle's boundary (outline) pixels and the pixels inside them, and the "perimeter" in formula (1) is the length connecting the perimeters (outer perimeters) of each of the boundary pixels. Boundary pixels are the pixels that make up the particle's outline. On the other hand, when the area of ​​a particle is 30 pixels or more, the "area" in formula (1) is the number of pixels remaining after subtracting half the number of boundary pixels from the area of ​​the particle, and the "perimeter" in formula (1) is the length connecting the perimeters (outer perimeters) of each of the boundary pixels.

[0038] As described above, the percentage of boron nitride (C1) in composition (X) is 10% by mass or more and 30% by mass or less. When this percentage is 10% by mass or more, it is easy to particularly increase the elastic modulus of the cured product. Furthermore, when this percentage is 30% by mass or less, the fluidity of composition (X) is not particularly likely to be impaired. It is more preferable that this percentage is 15% by mass or more. Furthermore, when the percentage is less than 20% by mass, it is possible to suitably suppress the increase in viscosity of composition (X) while realizing a good elastic modulus of the cured product.

[0039] The inorganic filler (C) may further contain a material other than boron nitride (C1). For example, the inorganic filler (C) may contain at least one selected from the group consisting of metal oxides such as silica, alumina, and titanium oxide, silicates such as talc, calcined clay, uncalcined clay, mica, and glass, carbonates such as calcium carbonate, magnesium carbonate, and hydrotalcite, hydroxides such as aluminum hydroxide, magnesium hydroxide, and calcium hydroxide, sulfates or sulfites such as barium sulfate, calcium sulfate, and calcium sulfite, borates such as zinc borate, barium metaborate, aluminum borate, calcium borate, and sodium borate, and nitrides such as aluminum nitride and silicon nitride.

[0040] When the inorganic filler (C) further contains a material other than boron nitride (C1), it is preferable that the inorganic filler (C) further contains a filler (C2) other than boron nitride (C1) having a median diameter of 0.1 μm or more and 2 μm or less and a circularity of 0.80 or more. In this case, when the median diameter of the filler (C2) is 2 μm or less and the circularity is 0.80 or more, the filler (C2) is unlikely to impair the fluidity of the composition (X). In addition, when the median diameter of the filler (C2) is 0.1 μm or more, the filler (C2) is unlikely to aggregate in the composition (X) and the cured product, and therefore the above-mentioned properties of the composition (X) and the cured product are unlikely to be impaired. The median diameter of the filler (C2) is more preferably 0.10 μm or more, and even more preferably 0.25 μm or more. In addition, the median diameter of the filler (C2) is more preferably 1.5 μm or less.

[0041] When the inorganic filler (C) contains the filler (C2), the total percentage of the boron nitride (C1) and the filler (C2) relative to the composition (X) is preferably 70% by mass or more and 85% by mass or less. When this percentage is 70% by mass or more, the thermal expansion coefficient of the cured product is particularly easily reduced, the thermal conductivity of the cured product is particularly easily increased, and the elastic modulus of the cured product is also likely to be an appropriate value. When this percentage is 85% by mass or less, the fluidity of the composition (X) is particularly unlikely to be hindered, and the elastic modulus of the cured product is particularly unlikely to become excessively large. It is more preferable that this percentage is less than 78% by mass.

[0042] It is particularly preferred that the filler (C2) contains α-alumina (C21). In this case, α-alumina (C21) is particularly likely to increase the thermal conductivity of the cured product while reducing the linear expansion coefficient of the cured product. When the filler (C2) contains α-alumina (C21), the total percentage of boron nitride (C1) and α-alumina (C21) relative to the composition (X) is preferably 70% by mass or more and 85% by mass or less. When this percentage is 70% by mass or more, it is easy to reduce the thermal expansion coefficient of the cured product, and it is easy to increase the thermal conductivity of the cured product, and further, it is easy to make the elastic modulus of the cured product a moderate value. Also, when this percentage is 85% by mass or less, the fluidity of the composition (X) is particularly unlikely to be hindered, and the elastic modulus of the cured product is particularly unlikely to become excessively large. It is more preferred that this percentage is less than 78% by mass.

[0043] Incidentally, α-alumina means alumina whose main crystal phase is the α phase. The main crystal phase is determined based on the CuKα characteristic X-ray diffraction pattern. In general, the α phase, θ phase, δ phase, γ phase, and κ phase, which are known as the crystalline phases of alumina, have peaks at the following positions in the CuKα characteristic X-ray diffraction pattern. The phase corresponding to the peak with the highest intensity among the peaks appearing at the following positions is regarded as the main crystal phase. In this embodiment, it is particularly preferable that the α crystallization rate of α-alumina (C21) is 80% or more. In this case, the thermal conductivity of the cured product is particularly likely to be increased. The α crystallization rate of alumina is defined as the ratio of the peak area of ​​the α phase to the sum of the peak areas of the crystalline phases of alumina (α phase, θ phase, δ phase, γ phase, and κ phase) appearing in the X-ray diffraction pattern of alumina, and is calculated from the results of X-ray diffraction measurement of alumina.

[0044] α phase: 2θ=57.5° θ phase: 2θ=32.7° δ phase: 2θ=36.5° γ phase: 2θ=45.4° Kappa phase: 2θ = 42.9°.

[0045] It is preferable that the inorganic filler (C) contains only boron nitride (C1) and filler (C2), and it is more preferable that the filler (C) contains only boron nitride (C1) and α-alumina (C21). The total percentage of boron nitride (C1) and filler (C2) to the filler (C) is preferably 97% by mass or more, more preferably 98% by mass or more, and even more preferably 99% by mass or more. In addition, the total percentage of boron nitride (C1) and α-alumina (C21) to the filler (C) is preferably 97% by mass or more, more preferably 98% by mass or more, and even more preferably 99% by mass or more.

[0046] It is preferable that the inorganic filler (C) does not contain scaly boron nitride, or that the inorganic filler (C) contains scaly boron nitride and the percentage of the scaly boron nitride in the composition (X) is more than 0 mass% and less than 3 mass%. In this case, anisotropy is particularly unlikely to occur in the composition (X), and therefore the viscosity and thixotropy of the composition (X) tend to be particularly low. It is more preferable that the percentage of the scaly boron nitride is 1 mass% or less.

[0047] The ratio of particles having a particle size of 5 μm or less in the inorganic filler (C) is preferably 99.9% by volume or more relative to the inorganic filler (C). In this case, the fluidity of the composition (X) is likely to be particularly high, and therefore voids are unlikely to occur in the plugged portion 1.

[0048] The composition (X) may further contain optional components other than those described above. The optional components include at least one selected from the group consisting of a coupling agent, a dispersant, and a curing accelerator.

[0049] The coupling agent can improve the wettability and adhesion at the interface between the epoxy resin (A) and the curing agent (B) and the inorganic filler (C). The coupling agent contains, for example, a silane coupling agent. The silane coupling agent contains, for example, at least one selected from the group consisting of N-phenyl-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and the like.

[0050] When composition (X) contains a coupling agent, composition (X) may be prepared by surface-treating inorganic filler (C) with a coupling agent and then mixing inorganic filler (C) with a material other than inorganic filler (C), or composition (X) may be prepared by mixing the coupling agent with a material other than the coupling agent without surface-treating inorganic filler (C) with a coupling agent.

[0051] The dispersant can enhance the dispersibility of the inorganic filler (C) in the composition (X) and in the cured product. The dispersant can include, for example, a phosphate polyester dispersant.

[0052] The curing accelerator can accelerate the reaction between the epoxy resin (A) and the curing agent (B) in the composition (X). The curing accelerator can contain an aluminum organic compound such as aluminum tris(acetylacetonate).

[0053] As described above, the composition (X) can be used to produce the sealing portion 1 in the semiconductor device 10. For example, the composition (X) is suitably used as an underfill material such as a capillary underfill material or a liquid molded underfill material, that is, as a material for producing an underfill. If the elastic modulus of the cured material constituting the underfill is high, internal stress is likely to occur, which may cause cracks. However, in the composition (X) according to this embodiment, the increase in viscosity is suppressed, and good fluidity during molding is ensured, and at the same time, a suitable elastic modulus can be achieved in the cured material after molding.

[0054] An example of a semiconductor device 10 including a sealing part 1 made from composition (X) is shown in Fig. 1. As described above, the semiconductor device 10 includes a substrate 3, an electronic component 2 mounted on the substrate 3, and a sealing part 1 that fills the gap between the substrate 3 and the electronic component 2. The sealing part 1 in Fig. 1 is an underfill. The sealing part 1 is a cured product of composition (X).

[0055] The substrate 3 is, for example, a mother substrate, a package substrate, or an interposer substrate. For example, the substrate 3 includes an insulating substrate made of glass epoxy, polyimide, polyester, ceramic, or the like, and a conductive conductor wiring made of copper or the like formed on the surface of the insulating substrate. The conductor wiring includes an electrode pad 5. The substrate 3 shown in FIG. 1 is provided with a solder resist 7. Also, a via 6 is formed in the substrate 3.

[0056] The electronic component 2 is, for example, a semiconductor chip. The semiconductor chip may be a bare chip or a semiconductor package. The semiconductor package is, for example, a flip-chip type chip such as a BGA (ball grid array), an LGA (land grid array), or a CSP (chip size package). The semiconductor chip may be a PoP (package on package) type chip. The electronic component 2 is provided with a plurality of bump electrodes 4. The bump electrodes 4 are formed of solder. The electronic component 2 is flip-chip mounted on the substrate 3. That is, the electronic component 2 is electrically connected to the electrode pads 5 of the substrate 3 through the bump electrodes 4.

[0057] The sealing portion 1 is filled into the gap between the substrate 3 and the electronic component 2 to seal this gap.

[0058] When manufacturing the semiconductor device 10, for example, first, the electronic component 2 is flip-chip mounted on the substrate 3. Next, the composition (X) is injected between the substrate 3 and the electronic component 2 using a capillary or the like while heating the composition (X) as necessary. The composition (X) flows through the gap between the substrate 3 and the electronic component 2 by capillary action and fills this gap. In this embodiment, the composition (X) can have good fluidity, and therefore the composition (X) is easily filled in the gap between the substrate 3 and the electronic component 2. In this state, the composition (X) is heated to harden it. As a result, the sealing portion 1 is produced, and the semiconductor device 10 including the sealing portion 1 is manufactured.

[0059] The sealing part 1 shown in FIG. 1 is an underfill, but the sealing part 1 does not have to be an underfill as long as at least a part of it fills the gap between the substrate 3 and the electronic component 2. For example, in the semiconductor device 10 shown in FIG. 1, the sealing part 1 may not only fill the gap between the substrate 3 and the electronic component 2, but may also cover the entire electronic component 2 to seal the entire electronic component 2. In this case, when manufacturing the semiconductor device 10, for example, the electronic component 2 is flip-chip mounted on the substrate 3. The substrate 3 and the electronic component 2 are set in a mold so that the electronic component 2 is placed in a cavity in the mold, and the composition (X) is injected into the cavity of the mold while being heated as necessary. The composition (X) fills around the electronic component 2 in the cavity of the mold, and flows through the gap between the substrate 3 and the electronic component 2 to fill the gap. At this time, the composition (X) can have good fluidity. In this state, the composition (X) is heated to harden it. As a result, the sealing part 1 is produced, and the semiconductor device 10 including the sealing part 1 is manufactured.

[0060] FIG. 1 shows an application example of so-called two-dimensional mounting in which chips are mounted on a substrate in a planar manner, but the composition (X) according to this embodiment can also be suitably used in so-called three-dimensional mounting, a mounting structure in which multiple chips (electronic components 2) are stacked. Since three-dimensional mounting tends to be more difficult to dissipate heat than two-dimensional mounting, a more suitable dimension is required to achieve both "high thermal conductivity" and "low stress". For example, HBM (high density memory) applications are known as three-dimensional mounting semiconductor devices, and liquid mold underfill materials are often used for underfill in HBM applications. The composition (X) according to this embodiment contains boron nitride (C1) as a component of the inorganic filler (C), which suppresses viscosity increase and ensures good fluidity, while realizing suitable high thermal conductivity and low stress (reduced elastic modulus) in the cured product. However, the viscosity tends to be somewhat higher than when only spherical alumina is used as the inorganic filler (C). However, since molding of liquid molded underfill materials is generally performed under pressure, there is a wide tolerance for viscosity increase, and when the composition (X) according to this embodiment is used in liquid molded underfill materials, the degree of freedom in blending boron nitride (C1) is high. In other words, in this case, it is permissible to increase the content of boron nitride (C1), so that it is possible to achieve both "high thermal conductivity" and "low stress" at a higher level. EXAMPLES

[0061] Specific examples of the present embodiment will be presented below. Note that the present embodiment is not limited to the following examples.

[0062] 1. Preparation of the Composition The raw materials shown in the composition column of Table 1 except for the curing agent and the curing accelerator were mixed, and these were stirred while degassing with a planetary mixer manufactured by Primix Corporation, and then kneaded with a three-roll mill. The curing agent and the curing accelerator were added to the mixture obtained in this way, and then mixed by stirring with the planetary mixer. In this way, a liquid composition was prepared. The details of the raw materials are as follows. -Epoxy resin #1: Bisphenol F type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd., product name Epotohto YDF-8170, viscosity at 25°C 1500 mPa·s, epoxy equivalent 160 g / eq. -Epoxy resin #2: Glycidylamine type epoxy resin, manufactured by ADEKA Corporation, product name ADEKA RESIN EP-3950S, viscosity at 25°C 650 mPa s, epoxy equivalent 95 g / eq. - Hardener #1: 3,3'-diethyl-4,4'-diaminodiphenylmethane, manufactured by Nippon Kayaku Co., Ltd., product name Kayahard AA. - Hardener #2: Aromatic polyamine, manufactured by Mitsubishi Chemical Corporation, product name JER Cure WA. -Spherical nano-sized boron nitride: manufactured by Denka Co., Ltd., median diameter 0.5 μm, average circularity 0.8. -Flake-shaped boron nitride: Manufactured by Showa Denko K.K., product name UHP-S2, median diameter 0.7 μm. -Alumina #1: Spherical α-alumina with α crystallization rate of 45%, median diameter 1.5 μm, average circularity = 0.95, BET specific surface area 2.4 m 2 / g. -Alumina #2: α-alumina with a polyhedral shape having an α crystallization rate of 100%, manufactured by Sumitomo Chemical Co., Ltd., product name AA-03F, median diameter 0.26 μm, cumulative 99% particle size 1.7 μm, average circularity 0.90, BET specific surface area 6.0 m 2 / g. - Hardening accelerator: Aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals, product name Aluminum Chelate A. -Silane coupling agent: γ-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd., product name KBM-403. -Dispersant: Phosphate polyester dispersant, manufactured by BYK Japan, product name DISPERBYK111, acid value 129mgKOH / g.

[0063] 2.Evaluation Test (1) Thermal conductivity The composition was heated at 100°C for 2 hours using a hot air dryer, and then heated at 160°C for 2 hours to cure the composition, producing a cured product. A sample having a square shape in plan view of 9.8mm x 9.8mm x 0.1mm was cut out from the cured product. A graphite spray (FC-153) manufactured by Fine Chemical Japan Co., Ltd. was sprayed onto the sample. The thermal diffusivity of the sample was measured using a xenon flash analyzer (manufactured by NETZSCH, product name NanoFlashLFA447). In addition, the density of the sample was measured by the Archimedes method, and the specific heat of the sample was measured by the DSC method. The thermal conductivity of the sample in the thickness direction was calculated by multiplying these thermal diffusivities, density, and specific heat.

[0064] (2) Glass transition temperature The composition was heated at 100°C for 2 hours using a hot air dryer, and then heated at 160°C for 2 hours to cure the composition, producing a cured product. A sample measuring 5 mm x 50 mm x 0.2 mm was cut out from the cured product. The glass transition temperature of the sample was measured using a viscoelasticity spectrometer (DMA) under the conditions of a bending mode, a frequency of 10 Hz, a heating rate of 2°C / min, and a temperature range of -60°C to 260°C.

[0065] (3) Linear expansion coefficient The composition was heated at 100°C for 2 hours using a hot air dryer, and then heated at 160°C for 2 hours to cure the composition, producing a cured product. A sample with dimensions of 70 mm or more in length, 10 mm in width, and 1 mm to 3 mm in thickness was cut out from this cured product. Using a thermomechanical analyzer (Seiko Instruments Inc., Model TMA / SS-6000), the sample was subjected to thermomechanical analysis at a heating rate of 5°C / min in a temperature range of -70°C to 260°C, and the linear expansion coefficient in the range of -55°C to 125°C was calculated from the results.

[0066] (4) Flexural modulus The composition was heated at 100°C for 2 hours using a hot air dryer, and then heated at 160°C for 2 hours to cure the composition, producing a cured product. A sample measuring 10 mm in width, 80 mm in length, and 3 mm in thickness was cut out from the cured product. A three-point bending test was performed on the sample using a universal tension and compression tester at a temperature of 25°C, a test speed of 2 mm / min, and a support distance of 48 mm, to measure the flexural modulus of the sample.

[0067] (5) Viscosity The viscosity of the epoxy resin composition was measured at 100° C. using a rheometer (TA Instruments Co., Ltd., model "DISCOVERY HR-2") with 25 mm aluminum parallel plates at a rotation speed of 5 rpm.

[0068] The results are shown in Table 1. Note that for Comparative Example 4, a sample could not be prepared due to high viscosity, and therefore evaluation tests other than for viscosity could not be carried out.

[0069] [Table 1]

[0070] As shown in the above results, in Examples 1 to 4, in which the inorganic filler in the composition contains spherical nano-sized boron nitride in a percentage of 10% by mass or more and 30% by mass or less, high thermal conductivity of the cured product, high glass transition temperature of the cured product, high linear expansion coefficient of the cured product, low flexural modulus of the cured product, and low viscosity of the composition were realized. In Examples 1 to 3, a particularly low viscosity of the composition was realized. Compared to these Examples 1 to 4, Comparative Examples 1 to 3, in which the inorganic filler in the composition contains only alumina, had a high flexural modulus, and Comparative Example 4, in which the inorganic filler does not contain spherical nano-sized boron nitride but contains scaly boron nitride, had a high viscosity.

Claims

1. An epoxy resin (A), A curing agent (B); and an inorganic filler (C), The epoxy resin (A) has a viscosity at 25°C of 1500 mPa s or less, The inorganic filler (C) contains boron nitride (C1) having a median diameter of 0.1 μm or more and 2 μm or less and an average circularity of 0.80 or more, The percentage of the boron nitride (C1) relative to the resin composition is 10% by mass or more and 30% by mass or less, The cured product of the resin composition has a flexural modulus at 25° C. of 10 GPa or less and a thermal conductivity of 1 W / m·K or more. Resin composition.

2. The inorganic filler (C) further contains a filler (C2) other than the boron nitride (C1) having a median diameter of 0.1 μm or more and 2 μm or less and a circularity of 0.80 or more. The resin composition according to claim 1.

3. The filler (C2) contains α-alumina (C21); The resin composition according to claim 2.

4. The inorganic filler (C) does not contain flaky boron nitride, or the inorganic filler (C) contains flaky boron nitride and the percentage of the flaky boron nitride relative to the resin composition is more than 0 mass% and less than 3 mass%. The resin composition according to claim 1 .

5. The percentage of the inorganic filler (C) relative to the resin composition is 70% by mass or more and 85% by mass or less; The resin composition according to any one of claims 1 to 4.

6. The curing agent (B) contains at least one of an aromatic amine and an acid anhydride. The resin composition according to any one of claims 1 to 5.

7. It is an underfill material. The resin composition according to any one of claims 1 to 6.

8. a substrate, an electronic component mounted on the substrate, and a sealing portion that seals the electronic component, wherein at least a portion of the sealing portion is filled in a gap between the substrate and the electronic component, The sealing portion is a cured product of the resin composition according to any one of claims 1 to 7. Semiconductor device.

Citation Information

Patent Citations

  • Epoxy resin molding material

    JP1989038423A

  • Thermally conductive composition and method for producing the same

    JP2008510878A

  • Epoxy resin composition, insulation sheet, and semiconductor module

    JP2018070687A

  • Underfill material, semiconductor package and method for manufacturing semiconductor package

    JP2019077771A

  • Resin composition, semiconductor device and method for producing semiconductor device

    JP2019167434A